Solvent-localized in-situ NMR Monitoring by Intermolecular Single-quantum Coherence Study - 차진욱; 박성혁 (한국자기공명학회, 2020)
A new NMR method to monitor solvent-localized NMR signals in the two-phase liquid system is suggested. This method based on intermolecular single-quantum coherence (iSQC). Here, we ex-ploited the feature of the local action of distant dipolar field (DDF) effect in order to filter out specific NMR signals dissolved in different sol-vents. This solvent specific iSQC spectroscopy was carried out on a model two-phase liquid sys-tem (D-glucose in water/palmitic acid in chloro-form), and showed solvent-localized NMR signals. We believe our approaches might be useful in metabolic analysis such as two-phase liquid ex-traction scheme for labile chemical species.